Waterproof and warm elastic knitted fabric, preparation method and application thereof in clothing
By using modified glue and modified filler agent in knitted fabrics, combined with nano titanium dioxide agent, the problem of insufficient performance of existing knitted fabrics is solved, and the fabric is highly elastic, good warm and waterproof, and durability is improved.
Patent Information
- Application Number
- CN202411985995.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The elasticity, warmth and waterproof properties of existing knitted fabrics are poor, and the durable performance is poor, which limits the efficiency of fabric products.
The modified glue is made of resin glue, modified filler and nano titanium dioxide, and is applied on cotton and modal blended yarn and mixed with polyester yarn to form a waterproof, warm elastic knitted fabric.
It significantly improves the elasticity, warmth and waterproof properties of the fabric, while enhancing the durable performance, which significantly improves the efficiency of fabric products.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of knitted fabrics, and in particular to a waterproof and warm elastic knitted fabric, a preparation method and application of the same in clothing. Background Art
[0002] Knitted fabrics are fabrics formed by bending yarns into loops and interlacing them with knitting needles. They are divided into warp knitted fabrics and weft knitted fabrics. Knitted fabrics are soft, breathable, perspiration-wicking and warm-keeping. Most of them have excellent elasticity and extensibility. Compared with woven fabrics, they have high production and are suitable for small batch production. Knitted clothing is comfortable to wear, fits the body, has no tightness, and can fully reflect the curves of the human body. Existing knitted fabrics have poor elasticity and thermal insulation properties. At the same time, the fabric products have weak waterproof properties, poor durability, and low stability, which limits the efficiency of fabric products. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a waterproof and warm stretch knitted fabric, a preparation method and its application in clothing, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a method for preparing a waterproof and warm elastic knitted fabric, comprising the following steps:
[0006] Step 1: 10-15 parts of resin glue, 4-7 parts of modified filler and 2-3 parts of nano titanium dioxide are mixed evenly by weight to obtain a modified glue; wherein the resin glue is obtained by mixing bisphenol A epoxy resin, silane coupling agent KH560, ethanol solvent and 2-methylimidazole in a weight ratio of 4:1:7:1;
[0007] Step 2: 45% by weight of cotton and 55% by weight of modal are blended to form a blended yarn, a modified adhesive solution is applied to the surface of the blended yarn, and then the blended yarn is dried at 65° C. for 2 hours to obtain a modified blended yarn body;
[0008] Step 3: The polyester yarn and the modified blended yarn are knitted into a fabric by a knitting machine in a weight ratio of 5:3, thereby obtaining a waterproof and warm stretch knitted fabric.
[0009] Preferably, the preparation method of the modified filler is:
[0010] S01: 3-5 parts of silane coupling agent KH550, 1-2 parts of ethanol and 4-7 parts of sodium citrate solution are fully mixed by weight to obtain a silane coupling agent liquid;
[0011] Stirring α-zirconium phosphate nanosheets in a sufficient amount of silane coupling agent liquid to obtain α-zirconium phosphate nanosheet liquid;
[0012] S02: Nano-silicon dioxide, glass fiber and lanthanum chloride solution are fully mixed in a weight ratio of 2:3:5, and then filtered and dried, and then heat-treated at 150-160° C. for 5 minutes, and then air-cooled to 55° C. to obtain an additive;
[0013] S03: The α-zirconium phosphate nanosheet liquid and the additives are mixed in a weight ratio of 5:2, and the mixture is ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.
[0014] Preferably, the mass fraction of the sodium citrate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-8%.
[0015] Preferably, the diameter of the α-zirconium phosphate nanosheets is 100-150 nm.
[0016] Preferably, the preparation method of the nano titanium dioxide agent is:
[0017] S11: Ultrasonic treatment of nano-titanium dioxide and fly ash liquid in a weight ratio of 3:5, with an ultrasonic power of 350-400 W for 1 h, and then the ultrasonic treatment is terminated to obtain fly ash / nano-titanium dioxide liquid;
[0018] S12: immersing the hollow glass microspheres into a sufficient amount of an auxiliary agent, stirring the mixture, and then filtering and drying the mixture to obtain a hollow glass microsphere agent; wherein the auxiliary agent is obtained by mixing a sodium dodecylbenzene sulfonate solution, stearic acid and lanthanum oxide in a weight ratio of 5:2:1;
[0019] S13: fly ash / nano titanium dioxide liquid and hollow glass microspheres are mixed in a weight ratio of 5:2 and subjected to ball milling at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano titanium dioxide agent.
[0020] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.
[0021] Preferably, the preparation method of the fly ash liquid is:
[0022] The sodium silicate solution, cerium oxide and nano-calcium carbonate are mixed in a weight ratio of 5:2:1 to obtain a treatment liquid; the fly ash is preheated at 55-60°C for 1 hour, and then added into the treatment liquid which is 3-5 times the total weight of the fly ash and stirred to obtain a fly ash liquid.
[0023] Preferably, the mass fraction of the sodium silicate solution is 4-7%.
[0024] The present invention also provides a waterproof and warm elastic knitted fabric, which is prepared by the preparation method of the waterproof and warm elastic knitted fabric.
[0025] The present invention also provides an application of the waterproof and warm elastic knitted fabric on clothing, and the waterproof and warm elastic knitted fabric is applied to clothing.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The knitted fabric of the present invention adopts 45% cotton and 55% modal to form a blended yarn, and then a modified glue liquid is applied, and the modified mixed yarn body is dried at 65°C for 2 hours to obtain a modified mixed yarn body. At the same time, polyester yarn and the modified mixed yarn body are blended and knitted to form the fabric of the present invention. The obtained fabric has excellent elasticity, warmth retention and waterproof properties, and the durable use performance of the fabric product is remarkable. The modified glue liquid is prepared by combining resin glue liquid, modified filler and nano titanium dioxide agent. The modified filler adopts alpha-zirconium phosphate nanosheets and is treated with a sufficient amount of silane coupling agent liquid. The silane coupling agent liquid is fully formed by blending silane coupling agent KH550, ethanol and sodium citrate solution, and the interfacial activity of the alpha-zirconium phosphate nanosheets is optimized, so as to better cooperate with additives for improvement. The nano-silicon dioxide, glass fiber and lanthanum chloride solution in the additive are mixed and then improved by heating, so that they can better coordinate with α-zirconium phosphate nanosheets. The modified filler uses α-zirconium phosphate nanosheets to carry nano-silicon dioxide and glass fiber to fill and reinforce the system, optimize the system performance, and improve the system performance stability. At the same time, the nano-titanium dioxide agent uses nano-titanium dioxide and fly ash liquid to be ultrasonically treated, and the hollow glass microspheres are treated with an additional agent composed of sodium dodecylbenzene sulfonate solution, stearic acid and lanthanum oxide to optimize the interface activity of the glass microspheres. At the same time, fly ash / nano-titanium dioxide liquid is combined to further reinforce the system structure and better coordinate the modified filler, so that the performance of the fabric product is further improved. DETAILED DESCRIPTION
[0028] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] A method for preparing a waterproof and warm stretch knitted fabric in this embodiment comprises the following steps:
[0030] Step 1: 10-15 parts of resin glue, 4-7 parts of modified filler and 2-3 parts of nano titanium dioxide are mixed evenly by weight to obtain a modified glue; wherein the resin glue is obtained by mixing bisphenol A epoxy resin, silane coupling agent KH560, ethanol solvent and 2-methylimidazole in a weight ratio of 4:1:7:1;
[0031] Step 2: 45% by weight of cotton and 55% by weight of modal are blended to form a blended yarn, a modified adhesive solution is applied to the surface of the blended yarn, and then the blended yarn is dried at 65° C. for 2 hours to obtain a modified blended yarn body;
[0032] Step 3: The polyester yarn and the modified blended yarn are knitted into a fabric by a knitting machine in a weight ratio of 5:3, thereby obtaining a waterproof and warm stretch knitted fabric.
[0033] The preparation method of the modified filler of this embodiment is:
[0034] S01: 3-5 parts of silane coupling agent KH550, 1-2 parts of ethanol and 4-7 parts of sodium citrate solution are fully mixed by weight to obtain a silane coupling agent liquid;
[0035] Stirring α-zirconium phosphate nanosheets in a sufficient amount of silane coupling agent liquid to obtain α-zirconium phosphate nanosheet liquid;
[0036] S02: Nano-silicon dioxide, glass fiber and lanthanum chloride solution are fully mixed in a weight ratio of 2:3:5, and then filtered and dried, and then heat-treated at 150-160° C. for 5 minutes, and then air-cooled to 55° C. to obtain an additive;
[0037] S03: The α-zirconium phosphate nanosheet liquid and the additives are mixed in a weight ratio of 5:2, and the mixture is ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.
[0038] The mass fraction of the sodium citrate solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 4-8%.
[0039] The diameter of the α-zirconium phosphate nanosheets of this embodiment is 100-150 nm.
[0040] The preparation method of the nano titanium dioxide agent of this embodiment is:
[0041] S11: Ultrasonic treatment of nano-titanium dioxide and fly ash liquid in a weight ratio of 3:5, with an ultrasonic power of 350-400 W for 1 h, and then the ultrasonic treatment is terminated to obtain fly ash / nano-titanium dioxide liquid;
[0042] S12: immersing the hollow glass microspheres into a sufficient amount of an auxiliary agent, stirring the mixture, and then filtering and drying the mixture to obtain a hollow glass microsphere agent; wherein the auxiliary agent is obtained by mixing a sodium dodecylbenzene sulfonate solution, stearic acid and lanthanum oxide in a weight ratio of 5:2:1;
[0043] S13: fly ash / nano titanium dioxide liquid and hollow glass microspheres are mixed in a weight ratio of 5:2 and subjected to ball milling at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano titanium dioxide agent.
[0044] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 2-5%.
[0045] The preparation method of the fly ash liquid of this embodiment is:
[0046] The sodium silicate solution, cerium oxide and nano-calcium carbonate are mixed in a weight ratio of 5:2:1 to obtain a treatment liquid; the fly ash is preheated at 55-60°C for 1 hour, and then added into the treatment liquid which is 3-5 times the total weight of the fly ash and stirred to obtain a fly ash liquid.
[0047] The mass fraction of the sodium silicate solution in this embodiment is 4-7%.
[0048] The waterproof and warm stretch knitted fabric of the present embodiment is prepared by the preparation method of the waterproof and warm stretch knitted fabric.
[0049] The present embodiment provides an application of a waterproof and warm stretch knitted fabric on clothing, and the waterproof and warm stretch knitted fabric is applied to clothing.
[0050] Embodiment 1: A method for preparing a waterproof and warm stretch knitted fabric, comprising the following steps:
[0051] Step 1: 10 parts of resin glue, 4 parts of modified filler and 2 parts of nano titanium dioxide are mixed evenly by weight to obtain a modified glue; wherein the resin glue is obtained by mixing bisphenol A epoxy resin, silane coupling agent KH560, ethanol solvent and 2-methylimidazole in a weight ratio of 4:1:7:1;
[0052] Step 2: 45% by weight of cotton and 55% by weight of modal are blended to form a blended yarn, a modified adhesive solution is applied to the surface of the blended yarn, and then the blended yarn is dried at 65° C. for 2 hours to obtain a modified blended yarn body;
[0053] Step 3: The polyester yarn and the modified blended yarn are knitted into a fabric by a knitting machine in a weight ratio of 5:3, thereby obtaining a waterproof and warm stretch knitted fabric.
[0054] The preparation method of the modified filler of this embodiment is:
[0055] S01: 3 parts of silane coupling agent KH550, 1 part of ethanol and 4 parts of sodium citrate solution are fully mixed by weight to obtain a silane coupling agent liquid;
[0056] Stirring α-zirconium phosphate nanosheets in a sufficient amount of silane coupling agent liquid to obtain α-zirconium phosphate nanosheet liquid;
[0057] S02: Nano-silicon dioxide, glass fiber and lanthanum chloride solution are fully mixed in a weight ratio of 2:3:5, and then filtered and dried, and then heat-treated at 150-160° C. for 5 minutes, and then air-cooled to 55° C. to obtain an additive;
[0058] S03: The α-zirconium phosphate nanosheet liquid and the additives are mixed in a weight ratio of 5:2, and the mixture is ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.
[0059] The mass fraction of the sodium citrate solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 4%.
[0060] The diameter of the α-zirconium phosphate nanosheets in this example is 100 nm.
[0061] The preparation method of the nano titanium dioxide agent of this embodiment is:
[0062] S11: Ultrasonic treatment of nano-titanium dioxide and fly ash liquid in a weight ratio of 3:5, with an ultrasonic power of 350 W for 1 h, and then the ultrasonic treatment is terminated to obtain fly ash / nano-titanium dioxide liquid;
[0063] S12: immersing the hollow glass microspheres into a sufficient amount of an auxiliary agent, stirring the mixture, and then filtering and drying the mixture to obtain a hollow glass microsphere agent; wherein the auxiliary agent is obtained by mixing a sodium dodecylbenzene sulfonate solution, stearic acid and lanthanum oxide in a weight ratio of 5:2:1;
[0064] S13: fly ash / nano titanium dioxide liquid and hollow glass microspheres are mixed in a weight ratio of 5:2 and subjected to ball milling at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano titanium dioxide agent.
[0065] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 2%.
[0066] The preparation method of the fly ash liquid of this embodiment is:
[0067] The sodium silicate solution, cerium oxide and nano-calcium carbonate are mixed thoroughly in a weight ratio of 5:2:1 to obtain a treatment liquid; the fly ash is preheated at 55°C for 1 hour, and then added into the treatment liquid which is 3 times the total weight of the fly ash and stirred evenly to obtain a fly ash liquid.
[0068] The mass fraction of the sodium silicate solution in this embodiment is 4%.
[0069] The waterproof and warm stretch knitted fabric of the present embodiment is prepared by the preparation method of the waterproof and warm stretch knitted fabric.
[0070] The present embodiment provides an application of a waterproof and warm stretch knitted fabric on clothing, and the waterproof and warm stretch knitted fabric is applied to clothing.
[0071] Embodiment 2: A method for preparing a waterproof and warm stretch knitted fabric, comprising the following steps:
[0072] Step 1: 15 parts of resin glue, 7 parts of modified filler and 3 parts of nano titanium dioxide are mixed evenly by weight to obtain a modified glue; wherein the resin glue is obtained by mixing bisphenol A epoxy resin, silane coupling agent KH560, ethanol solvent and 2-methylimidazole in a weight ratio of 4:1:7:1;
[0073] Step 2: 45% by weight of cotton and 55% by weight of modal are blended to form a blended yarn, a modified adhesive solution is applied to the surface of the blended yarn, and then the blended yarn is dried at 65° C. for 2 hours to obtain a modified blended yarn body;
[0074] Step 3: The polyester yarn and the modified blended yarn are knitted into a fabric by a knitting machine in a weight ratio of 5:3, thereby obtaining a waterproof and warm stretch knitted fabric.
[0075] The preparation method of the modified filler of this embodiment is:
[0076] S01: 5 parts of silane coupling agent KH550, 2 parts of ethanol and 7 parts of sodium citrate solution are fully mixed by weight to obtain a silane coupling agent liquid;
[0077] Stirring α-zirconium phosphate nanosheets in a sufficient amount of silane coupling agent liquid to obtain α-zirconium phosphate nanosheet liquid;
[0078] S02: Nano-silicon dioxide, glass fiber and lanthanum chloride solution are fully mixed in a weight ratio of 2:3:5, and then filtered and dried, and then heat-treated at 150-160° C. for 5 minutes, and then air-cooled to 55° C. to obtain an additive;
[0079] S03: The α-zirconium phosphate nanosheet liquid and the additives are mixed in a weight ratio of 5:2, and the mixture is ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.
[0080] The mass fraction of the sodium citrate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 8%.
[0081] The diameter of the α-zirconium phosphate nanosheets in this example is 150 nm.
[0082] The preparation method of the nano titanium dioxide agent of this embodiment is:
[0083] S11: Ultrasonic treatment of nano-titanium dioxide and fly ash liquid in a weight ratio of 3:5, with an ultrasonic power of 400 W for 1 h, and then the ultrasonic treatment is terminated to obtain fly ash / nano-titanium dioxide liquid;
[0084] S12: immersing the hollow glass microspheres into a sufficient amount of an auxiliary agent, stirring the mixture, and then filtering and drying the mixture to obtain a hollow glass microsphere agent; wherein the auxiliary agent is obtained by mixing a sodium dodecylbenzene sulfonate solution, stearic acid and lanthanum oxide in a weight ratio of 5:2:1;
[0085] S13: fly ash / nano titanium dioxide liquid and hollow glass microspheres are mixed in a weight ratio of 5:2 and subjected to ball milling at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano titanium dioxide agent.
[0086] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 5%.
[0087] The preparation method of the fly ash liquid of this embodiment is:
[0088] The sodium silicate solution, cerium oxide and nano-calcium carbonate are mixed thoroughly in a weight ratio of 5:2:1 to obtain a treatment liquid; the fly ash is preheated at 60°C for 1 hour, and then added into the treatment liquid which is 5 times the total weight of the fly ash and stirred evenly to obtain a fly ash liquid.
[0089] The mass fraction of the sodium silicate solution in this embodiment is 7%.
[0090] The waterproof and warm stretch knitted fabric of the present embodiment is prepared by the preparation method of the waterproof and warm stretch knitted fabric.
[0091] The present embodiment provides an application of a waterproof and warm stretch knitted fabric on clothing, and the waterproof and warm stretch knitted fabric is applied to clothing.
[0092] Embodiment 3: A method for preparing a waterproof and warm stretch knitted fabric, comprising the following steps:
[0093] Step 1: 12.5 parts of resin glue, 5.5 parts of modified filler and 2.5 parts of nano titanium dioxide are mixed evenly by weight to obtain a modified glue; wherein the resin glue is obtained by mixing bisphenol A epoxy resin, silane coupling agent KH560, ethanol solvent and 2-methylimidazole in a weight ratio of 4:1:7:1;
[0094] Step 2: 45% by weight of cotton and 55% by weight of modal are blended to form a blended yarn, a modified adhesive solution is applied to the surface of the blended yarn, and then the blended yarn is dried at 65° C. for 2 hours to obtain a modified blended yarn body;
[0095] Step 3: The polyester yarn and the modified blended yarn are knitted into a fabric by a knitting machine in a weight ratio of 5:3, thereby obtaining a waterproof and warm stretch knitted fabric.
[0096] The preparation method of the modified filler of this embodiment is:
[0097] S01: 4 parts of silane coupling agent KH550, 1.5 parts of ethanol and 5.5 parts of sodium citrate solution are fully mixed by weight to obtain a silane coupling agent liquid;
[0098] Stirring α-zirconium phosphate nanosheets in a sufficient amount of silane coupling agent liquid to obtain α-zirconium phosphate nanosheet liquid;
[0099] S02: Nano-silicon dioxide, glass fiber and lanthanum chloride solution are fully mixed in a weight ratio of 2:3:5, and then filtered and dried, and then heat-treated at 155° C. for 5 minutes, and then air-cooled to 55° C. to obtain an additive;
[0100] S03: The α-zirconium phosphate nanosheet liquid and the additives are mixed in a weight ratio of 5:2, and the mixture is ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.
[0101] The mass fraction of the sodium citrate solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 6%.
[0102] The diameter of the α-zirconium phosphate nanosheets in this example is 125 nm.
[0103] The preparation method of the nano titanium dioxide agent of this embodiment is:
[0104] S11: Ultrasonic treatment of nano-titanium dioxide and fly ash liquid in a weight ratio of 3:5, with an ultrasonic power of 375 W, for 1 h, and then the ultrasonic treatment is terminated to obtain fly ash / nano-titanium dioxide liquid;
[0105] S12: immersing the hollow glass microspheres into a sufficient amount of an auxiliary agent, stirring the mixture, and then filtering and drying the mixture to obtain a hollow glass microsphere agent; wherein the auxiliary agent is obtained by mixing a sodium dodecylbenzene sulfonate solution, stearic acid and lanthanum oxide in a weight ratio of 5:2:1;
[0106] S13: fly ash / nano titanium dioxide liquid and hollow glass microspheres are mixed in a weight ratio of 5:2 and subjected to ball milling at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano titanium dioxide agent.
[0107] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 3.5%.
[0108] The preparation method of the fly ash liquid of this embodiment is:
[0109] The sodium silicate solution, cerium oxide and nano-calcium carbonate are mixed thoroughly in a weight ratio of 5:2:1 to obtain a treatment liquid; the fly ash is preheated at 57.5°C for 1 hour, and then added into the treatment liquid which is 4 times the total weight of the fly ash and stirred evenly to obtain a fly ash liquid.
[0110] The mass fraction of the sodium silicate solution in this embodiment is 5.5%.
[0111] The waterproof and warm stretch knitted fabric of the present embodiment is prepared by the preparation method of the waterproof and warm stretch knitted fabric.
[0112] The present embodiment provides an application of a waterproof and warm stretch knitted fabric on clothing, and the waterproof and warm stretch knitted fabric is applied to clothing.
[0113] The elastic properties of the fabric products of Examples 1-3 were tested, and the test results are shown in Table 1.
[0114] Table 1 Elasticity performance test results of fabric products of Examples 1-3:
[0115]
[0116] It can be seen from Table 1 that the fabric products of Examples 1-3 of the present invention have excellent elastic properties.
[0117] Comparative Example 1:
[0118] The difference from Example 3 is that the blended yarn is not treated with modified rubber solution.
[0119] Comparative Example 2:
[0120] The difference from Example 3 is that no modified filler is added to the modified rubber solution.
[0121] Comparative Example 3:
[0122] The difference from Example 3 is that no α-zirconium phosphate nanosheet liquid is added to the modified filler.
[0123] Comparative Example 4:
[0124] The difference from Example 3 is that no additive is added to the α-zirconium phosphate nanosheet liquid.
[0125] Comparative Example 5:
[0126] The difference from Example 3 is that glass fiber and lanthanum chloride solution are not added into the additive.
[0127] Comparative Example 6:
[0128] The difference from Example 3 is that no nano titanium dioxide agent is added to the modified glue.
[0129] Comparative Example 7:
[0130] The difference from Example 3 is that no hollow glass microspheres are added to the nano titanium dioxide agent.
[0131] Comparative Example 8:
[0132] The difference from Example 3 is that no additional agent treatment is used in the preparation of the hollow glass microspheres.
[0133] Comparative Example 9:
[0134] The difference from Example 3 is that fly ash / nano titanium dioxide liquid is not added to the nano titanium dioxide agent.
[0135] Comparative Example 10:
[0136] The difference from Example 3 is that no nano titanium dioxide is added to the fly ash / nano titanium dioxide liquid.
[0137] Comparative Example 11:
[0138] The difference from Example 3 is that the treatment liquid in the fly ash liquid is replaced by water.
[0139] Comparative Example 12:
[0140] The difference from Example 3 is that no cerium oxide and nano calcium carbonate are added to the treatment solution.
[0141] The fabric products of Examples 1 to 3 and Comparative Examples 1 to 12 were tested for thermal insulation performance, waterproof performance, and durability performance (the fabrics were washed 10 times and then irradiated with UV light for 48 hours at an intensity of 400 w / cm 2 ), the test results are shown in Table 2.
[0142] Table 2 Fabric product performance test results of Examples 1 to 3 and Comparative Examples 1 to 12:
[0143]
[0144] It can be seen from comparative examples 1 to 12 and embodiments 1 to 3 that the fabric product of embodiment 3 of the present invention has excellent warmth retention rate and water repellency level, and at the same time, the durable use performance effect is remarkable, the warmth retention and waterproofness of the fabric product can be improved in a coordinated manner, and at the same time, the elastic performance effect of the fabric product is excellent;
[0145] It can be seen from Comparative Examples 1 to 12 and Example 3 that the blended yarn is not treated with modified glue, and the performance of the fabric product shows a significant trend of deterioration;
[0146] The modified glue liquid without adding the modified filler and the modified glue liquid without adding the nano titanium dioxide agent has a significant deterioration trend in the performance of the fabric products. The modified glue liquid obtained by using the modified filler and the nano titanium dioxide agent of the present invention has the most significant performance effect on the fabric products.
[0147] The performance of fabric products tended to deteriorate when no α-zirconium phosphate nanosheet liquid was added to the modified filler, no additives were added to the α-zirconium phosphate nanosheet liquid, and no glass fiber and lanthanum chloride solution were added to the additives;
[0148] The hollow glass microspheres were not added to the nano titanium dioxide agent, the hollow glass microspheres were not treated with additional agents in their preparation, the fly ash / nano titanium dioxide liquid was not added to the nano titanium dioxide agent, the fly ash / nano titanium dioxide liquid was not added with nano titanium dioxide, the treatment liquid in the fly ash liquid was replaced with water, and cerium oxide and nano calcium carbonate were not added to the treatment liquid. The performance of the fabric products showed a trend of deterioration to varying degrees.
[0149] The nano titanium dioxide agent obtained by combining the fly ash / nano titanium dioxide liquid obtained by the specific method of the present invention with the hollow glass microsphere agent has the most significant effect on the performance of fabric products. Other methods are not as obvious as the present invention.
[0150] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0151] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a waterproof and warm elastic knitted fabric, characterized in that: The following steps are involved: Step 1: 10-15 parts of resin glue, 4-7 parts of modified filler and 2-3 parts of nano titanium dioxide are mixed evenly by weight to obtain a modified glue; wherein the resin glue is obtained by mixing bisphenol A epoxy resin, silane coupling agent KH560, ethanol solvent and 2-methylimidazole in a weight ratio of 4:1:7:1; Step 2: 45% by weight of cotton and 55% by weight of modal are blended to form a blended yarn, a modified adhesive is applied to the surface of the blended yarn, and then the blended yarn is dried at 65° C. for 2 hours to obtain a modified blended yarn; Step 3: knitting the polyester yarn and the modified blended yarn into a fabric through a knitting machine at a weight ratio of 5:3, thereby obtaining a waterproof and warm stretch knitted fabric; The preparation method of the modified filler is: S01: 3-5 parts of silane coupling agent KH550, 1-2 parts of ethanol and 4-7 parts of sodium citrate solution are fully mixed by weight to obtain a silane coupling agent solution; Stirring α-zirconium phosphate nanosheets in a sufficient amount of silane coupling agent liquid to obtain α-zirconium phosphate nanosheet liquid; S02: Nano-silicon dioxide, glass fiber and lanthanum chloride solution are fully mixed in a weight ratio of 2:3:5, and then filtered and dried, and then heat-treated at 150-160° C. for 5 minutes, and then air-cooled to 55° C. to obtain an additive; S03: The α-zirconium phosphate nanosheet liquid and the additive are mixed in a weight ratio of 5:2, and the ball milling is carried out at a ball milling speed of 1000r / min for 2h. After the ball milling is completed, the mixture is filtered and dried to obtain a modified filler; the mass fraction of the sodium citrate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-8%; and the sheet diameter of the α-zirconium phosphate nanosheet is 100-150nm.
2. The method for preparing the waterproof and warm elastic knitted fabric according to claim 1, characterized in that: The preparation method of the nano titanium dioxide agent is: S11: Ultrasonic treatment of nano-titanium dioxide and fly ash liquid in a weight ratio of 3:5, with an ultrasonic power of 350-400 W for 1 h, and then the ultrasonic treatment is terminated to obtain fly ash / nano-titanium dioxide liquid; S12: immersing the hollow glass microspheres into a sufficient amount of an auxiliary agent, stirring the mixture, and then filtering and drying the mixture to obtain a hollow glass microsphere agent; wherein the auxiliary agent is obtained by mixing a sodium dodecylbenzene sulfonate solution, stearic acid and lanthanum oxide in a weight ratio of 5:2:1; S13: fly ash / nano titanium dioxide liquid and hollow glass microspheres are mixed in a weight ratio of 5:2 and subjected to ball milling at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano titanium dioxide agent.
3. The method for preparing the waterproof and warm elastic knitted fabric according to claim 2, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.
4. The method for preparing the waterproof and warm elastic knitted fabric according to claim 2, characterized in that: The preparation method of the fly ash liquid is: The sodium silicate solution, cerium oxide and nano-calcium carbonate are mixed in a weight ratio of 5:2:1 to obtain a treatment liquid; the fly ash is preheated at 55-60°C for 1 hour, and then added into the treatment liquid which is 3-5 times the total weight of the fly ash and stirred to obtain a fly ash liquid.
5. The method for preparing the waterproof and warm elastic knitted fabric according to claim 4, characterized in that: The mass fraction of the sodium silicate solution is 4-7%.
6. A waterproof and warm elastic knitted fabric, characterized in that: The waterproof and warm stretch knitted fabric is prepared by the preparation method of any one of claims 1 to 5.
7. Application of a waterproof and warm elastic knitted fabric in clothing, characterized in that: The waterproof and warm stretch knitted fabric described in claim 6 is applied to clothing.
Citation Information
Patent Citations
Formula of knitted fabric slurry
CN108951151A
Anti-pilling knitted fabric and preparation method thereof
CN119162832A